2020
DOI: 10.3390/en13246574
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Impacts of Potential CO2 and Brine Leakage on Groundwater Quality with Quantitative Risk Assessment: A Case Study of the Farnsworth Unit

Abstract: Potential leakage of reservoir fluids is considered a key risk factor for geologic CO2 sequestration (GCS), with concerns of their chemical impacts on the quality of overlying underground sources of drinking water (USDWs). Effective risk assessment provides useful information to guide GCS activities for protecting USDWs. In this study, we present a quantified risk assessment case study of an active commercial-scale CO2-enhanced oil recovery (CO2-EOR) and sequestration field, the Farnsworth Unit (FWU). Specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 59 publications
0
16
0
Order By: Relevance
“…Xiao et al [18] present a quantified risk assessment case study of the FWU that identifies water chemistry indicators for early leak detection and includes the use of response surface methodology (RSM) to quantify potential risks of CO 2 and brine leakage to the overlying USDW quality. Salient findings include: (1) with a leakage flux up to 0.4% of injected CO 2 and brine from a conceptual leaky well with failure, it is likely that the impacted area is limited to within 50 m from the well after 200 years; (2) toxic trace metals may be considered an insignificant long-term concern because of clay adsorption; (3) site-specific, no-impact thresholds could be a preferable reference for groundwater quality evaluations; and (4) pH is suggested as a likely geochemical indicator for early detection of a leakage, due to its easy testing and sensitivity aspects.…”
Section: Riskmentioning
confidence: 99%
“…Xiao et al [18] present a quantified risk assessment case study of the FWU that identifies water chemistry indicators for early leak detection and includes the use of response surface methodology (RSM) to quantify potential risks of CO 2 and brine leakage to the overlying USDW quality. Salient findings include: (1) with a leakage flux up to 0.4% of injected CO 2 and brine from a conceptual leaky well with failure, it is likely that the impacted area is limited to within 50 m from the well after 200 years; (2) toxic trace metals may be considered an insignificant long-term concern because of clay adsorption; (3) site-specific, no-impact thresholds could be a preferable reference for groundwater quality evaluations; and (4) pH is suggested as a likely geochemical indicator for early detection of a leakage, due to its easy testing and sensitivity aspects.…”
Section: Riskmentioning
confidence: 99%
“…For the sake of brevity, please refer to previous publications for the details of CO 2 sequestration at the FWU. For example, Ross-Coss et al, 2015 and Ampomah et al, 2016 focused on geological characterization performed at the FWU [26,32]; Kumar et al, 2018 andBalch et al, 2017 presented MVA findings at the FWU [28,33]; Ampomah et al, 2016, Moodie et al, 2017, and Moodie et al, 2019 presented numerical simulation results for GCS forecast at the FWU [34][35][36]; and Dai et al, 2016, and Xiao et al, 2020 addressed uncertainty analysis due to both geological and operational factors and quantitative risk assessment of CO 2 leakage and its impact on overlying underground sources of drinking water [16,17,[37][38][39]. This study is built upon this previous FWU work and focuses on risk assessments associated with reactive transport, in particular mineral reactive surface areas.…”
Section: Fwu Descriptionmentioning
confidence: 99%
“…Existing uncertainty studies for GCS primarily focus on uncertainties stemming from porosity, permeability, and operational factors (e.g., injection scheme) [6,[14][15][16][17][18][19][20]. Only a few studies have examined the impact of uncertain reactive surface areas on GCS performances.…”
Section: Introductionmentioning
confidence: 99%
“…One of the main concerns with geologic CO2 sequestration (GCS) projects is the potential risks of CO2 and brine leakage to overlying resources (e.g., underground sources of drinking water (USDW), hydrocarbon and mineral resources) (Benson and Myer, 2003;Harp et al, 2016;Xiao et al, 2020). To build confidence of stakeholder, a scientific approach to quantitatively manage risk is needed to provide accurate predictions of long-term risks of CO2 sequestration systems (Condor et al, 2011;Pawar et al, 2013;De Lary et al, 2015;Li and Liu, 2016;Pawar et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…They found that the potential amount of CO2 leaked is affected by permeability, residual CO2 saturation, CO2 relative permeability hysteresis, confining rock permeability, and capillary pressure. Xiao et al (2020) conducted risk assessment for an active CO2 enhanced oil recovery (EOR) field, The Farnsworth Unit in Texas. The CO2 and brine leakage risks to the overlying USDW were quantified with a proxy modeling approach.…”
Section: Introductionmentioning
confidence: 99%